Nutrisi pada pengguna gigitiruan penuh Nutrition for the wearer of full denture - Nur Huda Alimin; Hermiati Daharudin; Harlina Harlina (Journal of Dentomaxillofacial Science, 2013)
People’s health mainly depends on the intake of nutrients intake. It is well known that tooth loss affects health,although it could be restored by prosthodontic treatment. Denture wearer’s diet usually consists of soft foods. This kindof diet will limit the variety of foods consumed by the elderly, and increasing the risk of nutrition deficiencies.Inadequate nutrition for a long time could lead to various kinds of diseases, even the systemic, which primarily occursin the mouth because of clinical symptoms of early malnutrition firstly found in the mouth. The risk of nutritionalemergencies could increase along with the aging. The understanding of nutritional supply, consumption problem ofelderly, and symptoms of nutrition disorder could help dentists identifying denture patiens with nutrition disorder riskand could give solutions for them.